PENGARUH BACK ROLLING MASSAGE TERHADAP PENINGKATAN BERAT BADAN SAMPAI USIA 6 BULAN - Paryono Paryono; Lusinta Agustina; Eka Puspita Rossa Amanda (Tahta Media Group, 2024)
Background, The problem of mothers not consistently giving breast milk is the mother's fear of the adequacy of the breast milk produced. Efforts to increase the adequacy of breast milk so that the baby's weight increases can be done with back rolling massage. Massage in this spinal area increases blood flow, provides a sense of comfort, stimulates milk production, overcomes the inactivity of breast milk production which is assisted by the baby's suction on the nipple. Purpose, This study is to determine the effect of back rolling massage on the weight gain of infants aged 0-6 months in the Working Area of the Kartasura Health Center. Methodology, This type of research uses Quasy Experimental with pretest-posttest with control group design. The number of samples in this study is 30 respondents. Data collection was carried out with observation sheets. The data analysis of this study was by univariate and bivariate analysis by Wilcoxon. Results : Based on the research, the results obtained by using the Wilcoxon test obtained a value r= 0.005 for the control group and a value r= 0.001 for the intervention group, where the value value r < α (0.05) which means that there is an effect of back rolling massage on the weight gain of infants aged 0-6 months in the Working Area of the Kartasura Health Center. Conclusion : There is an effect of back rolling massage on the weight gain of infants aged 0-6 months in the Working Area of the Kartasura Health Center.